2018
DOI: 10.1371/journal.pone.0190588
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of bacterial pathogens to evoking serological disease markers and aggravating disease activity in rheumatoid arthritis

Abstract: Commensal bacteria and their pathogenic components in the gastrointestinal tract and oral cavity may play pathological roles in autoimmune diseases. To study the possible involvement of bacterial pathogens in autoimmune diseases, IgG and IgA antibodies against pathogenic components produced by three strains of commensal bacteria, Escherichia coli-lipopolysaccharide (E. coli-LPS), Porphyromonas gingivalis-LPS (Pg-LPS) and peptidoglycan polysaccharide (PG-PS) from Streptococcus pyogenes, were determined by an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 77 publications
2
10
1
Order By: Relevance
“…An example which may be used is the above observation that, in patients treated MTX, reaction with Lys-GalA and O3 LPS was lower. Results obtained with the correlation of MTX treatment and sera reactivity do not confirm earlier studies that show that MTX treatment patients had increased reaction with LPS of environment bacteria [ 5 ].…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…An example which may be used is the above observation that, in patients treated MTX, reaction with Lys-GalA and O3 LPS was lower. Results obtained with the correlation of MTX treatment and sera reactivity do not confirm earlier studies that show that MTX treatment patients had increased reaction with LPS of environment bacteria [ 5 ].…”
Section: Discussioncontrasting
confidence: 83%
“…It is believed that RA development is dependent on genetic factors, HLA polymorphisms, and environmental factors such as smoking and infectious agents [ 4 ]. It is assumed that autoimmunity caused by infective agents is induced by molecular mimicry, cross-reactions, or the formation of immunological complexes [ 5 ]. One of the most common bacteria linked with the etiopathogenesis and development of RA is Proteus mirabilis .…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria number changes in the intestinal flora including these bacteria might be closely related to the effectiveness of MTX and remission of RA. Our report indicated that the IgA and IgG levels against P. gingivalis significantly increased in sera from RA patients treated with MTX for a long period, suggesting MTX may change the intestinal bacterial balance including P. gingivalis [20,100,105]. As previously described, immune suppressed mice become highly susceptible against LPS toxicity and develop severe and destructive arthritis with a single IP injection of LPS.…”
Section: Studies Of the Adverse Effects Of Antiautoimmune Drugs Thatsupporting
confidence: 77%
“…RA patients harboring the HLA-DR4 gene with severe arthritic inflammation have low levels of anti-type II collagen autoantibodies, in contrast to CIA-susceptible DBA/1 mice. Therefore, RA can be characterized into two types, both of which are related to environmental factors, but differ regarding how antibodies induce pathology [ 19 , 20 ].…”
Section: Cia and Caia As Animal Models Of Ramentioning
confidence: 99%
See 1 more Smart Citation